Genetic and Physical Interactions between Gα Subunits and Components of the Gβγ Dimer of Heterotrimeric G Proteins in Neurospora crassa - Won, Susan (American Society for Microbiology, 2012)
Heterotrimeric G proteins are critical regulators of growth and asexual and sexual development in the filamentous fungus Neurospora crassa. Three Gα subunits (GNA-1, GNA-2, and GNA-3), one Gβ subunit (GNB-1), and one Gγ subunit (GNG-1) have been functionally characterized, but genetic epistasis relationships between Gβ and Gα subunit genes have not been determined. Physical association between GNB-1 and FLAG-tagged GNG-1 has been previously demonstrated by coimmunoprecipitation, but knowledge of the Gα binding partners for the Gβγ dimer is currently lacking. In this study, the three N. crassa Gα subunits are analyzed for genetic epistasis with gnb-1 and for physical interaction with the Gβγ dimer. We created double mutants lacking one Gα gene and gnb-1 and introduced constitutively active, GTPase-deficient alleles for each Gα gene into the Δgnb-1 background. Genetic analysis revealed that gna-3 is epistatic to gnb-1 with regard to negative control of submerged conidiation. gnb-1 is epistatic to gna-2 and gna-3 for aerial hyphal height, while gnb-1 appears to act upstream of gna-1 and gna-2 during aerial conidiation. None of the activated Gα alleles restored female fertility to Δgnb-1 mutants, and the gna-3(Q208L) allele inhibited formation of female reproductive structures, consistent with a need for Gα proteins to cycle through the inactive GDP-bound form for these processes. Coimmunoprecipitation experiments using extracts from the gng-1-FLAG strain demonstrated that the three Gα proteins interact with the Gβγ dimer. The finding that the Gβγ dimer interacts with all three Gα proteins is supported by epistasis between gnb-1 and gna-1, gna-2, and gna-3 for at least one function.